Planning the Electrification of Rural Villages in East Nusa Tenggara Using Renewable Energy Generation - Jannata Giwangkara; Bart van Campen (Indonesian Journal of Energy, 2018)
Providing accessible, affordable and renewable electricity to rural areas in developing countries like Indonesia, is arguably challenging. The higher initial cost of renewable, as compared to conventional energy technologies, is often viewed as an obstacle in the rural electrification decision-making process. This study is conducted to examine the techno-economic feasibility of renewable energy generation options to bring electricity to the rural villages in Indonesia with Belu Regency, East Nusa Tenggara (ENT) as a case study. In this study, three village electrification scenarios were generated: basic (with the demand load of 150,5 kWh/day), moderate (359,9 kWh/day) and advanced electrification (579 kWh/day). To supply the load, three energy technologies were compared: conventional technology (diesel-powered); renewables technology (solar PV, and wind turbines); and hybrid technology (combination of diesel, solar PV and wind). The Hybrid Optimization of Multiple Energy Resource (HOMER) software was selected to model the best-optimised system configuration for the scenarios with defined constraints and sensitivity analysis. The study also investigates the impact and benefit of each system on the environment, specifically on CO2 emissions and pricing options. The results found that the renewable energy village-grid system (mostly powered by solar PV) is more competitive than the diesel-powered system in all scenarios. The levelized cost of energy (LCOE) of renewable energy system for each scenario is 0,66 USD/kWh (basic), 0,74 USD/kWh (moderate) and 0,55 USD/kWh (advance) respectively. This preliminary study concludes that rural electrification with renewables is a feasible option for a generic, modeled village in ENT. More, specific case research would be needed. JEL Classification: Q42, Q54